CILI as a source of inspiration for ideas for crating work of fine art - Utama, Pande Komang Budhi Sastra; Setem, I Wayan; Kondra, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2025)
This report describes the creation of works of painting with the theme "Cili as a source of inspiration for ideas for creating works of fine art", which was inspired by the unique shape of a cili, a ceremony in agrarian life that is involved in most people. In this case, Cili is a symbol of the transformation of the Goddess Sri into the Goddess of Fertility, Prosperity of the Mother Goddess or Mother Earth, from the land or Mother Earth all human needs emerge, for example plants and others. Cili is a symbol that is closely related to life and fertility. sometimes cili is associated with the goddess Sri, the goddess of rice, who symbolizes fertility. The meaning of chili in Balinese culture is closely related to the ceremonies in agricultural life that most people participate in. In this case, chili becomes a symbol of the reproduction of Dewi Sri as the goddess of fertility, prosperity of the Mother Goddess or Mother Earth, from whom the land or Mother Earth produces all human needs, for example plants and others. In the creation process using steps: basic research, exploration, improvisation. In the process of creating the work, the author took references from the Wasundari Kamasan studio as a source for creating the work. The author combines the given ornaments. In the creation process the author took the shape of water, the shape of rocks, and the shape of a tree.